Integrative cognitive remediation for early psychosis: A 12-month follow-up. (June 2020) - Vidarsdottir, Olina G.; Twamley, Elizabeth W.; Roberts, David L.; Sigurdsson, Engilbert; Gudmundsdottir, Berglind; Magnusdottir, Brynja B.
Highlights: Long-term effects of integrated cognitive remediation (ICR) for early psychosis. Significant improvements on many neuro- and social-cognitive domains. Gains maintained over one year for verbal memory and processing speed. Significant improvements on number of participants employed. Abstract: In recent years, a growing number of studies have attempted to treat social-cognitive impairment within neurocognitive remediation as means of improving outcome in psychotic disorders with promising results. However, the durability of the effects is still under debate and little is known about the long-term efficacy of integrated neuro- and social-cognitive remediation in early psychosis. The purpose of this study was to examine long-term effects of a 12-week integrative cognitive remediation (ICR) for early psychosis. Thirty-seven patients diagnosed with primary psychotic disorder and previously treated with ICR as part of their standard treatment were assessed on cognitive performance, psychopathology, and functional outcome at baseline, 3 months (posttest) and 12 months (follow-up). After participating in ICT, individuals showed significant improvements on most neurocognitive and social cognitive domains. A significant increase in number of participants employed was found at 12-month. The study suggests ICR may have favorable effect on long-term cognitive improvements and functional gains in early psychosis.